Australian Election Study, 1996 - Jones, Roger (ADA Dataverse, 2017)
The 1996 Australian Election Study is the fourth in a series of surveys beginning in 1987 which have been timed to coincide with Australian Federal elections. The series also builds on the 1967 and 1979 Australian Political Attitudes Surveys. The Australian Election Studies aim to provide a long-term perspective on stability and change in the political attitudes and behaviour of the Australian electorate, and investigate the changing social bases of Australian politics as the economy and society modernise and change character. In addition to these long-term goals they examine the political issues prevalent in the election and assesses their importance for the election result. The 1996 survey replicates many questions from the 1987, 1990 and 1993 Australian Election Studies, but also introduces a variety of new questions including a section on national identity. Other sections covered the respondent's interest in the election campaign and politics, their past and present political affiliation, evaluation of parties and candidates, alignment with parties on various election issues, evaluation of the economic situation and economic policies, attitudes to a range of environmental issues, attitudes to foreign affairs and defence issues and attitudes to contemporary social policy issues including equal opportunity, censorship, migration, assistance for aborigines, abortion, criminal law, expenditure on social services, the monarchy and the Australian flag. Background variables include level of education, employment status, occupation, type of employer, position at workplace, trade union membership, sex, age, own and parents country of birth, parents' political preferences, religion, marital status, income, and where applicable, the occupation, trade union membership and political preference of the respondent's spouse.